Answer:
16.9%
Step-by-step explanation:
Let's find the answer by using the following formula:
final people=(initial people)+((initial people)*(percent increase)) which can be written as:
percent increase=((final people)-(initial people))/(initial people) so:
percent increase=(83-71)/71=0.169=16.9%
In conclusion, the percent increase is 16.9%.
Answer:
3y
Step-by-step explanation:
Answer:
$120
Step-by-step explanation:
150-20%
For some reason it says that my response has to be 20 characters long that's why I'm typing this.